Effects of gasoline and ethanol-gasoline exhaust exposure on human bronchial epithelial and natural killer cells in vitro. (December 2017) - Roth, Michèle; Usemann, Jakob; Bisig, Christoph; Comte, Pierre; Czerwinski, Jan; Mayer, Andreas C.R.; Beier, Konstantin; Rothen-Rutishauser, Barbara; Latzin, Philipp; Müller, Loretta
Abstract: Air pollution exposure, including passenger car emissions, may cause substantial respiratory health effects and cancer death. In western countries, the majority of passenger cars are driven by gasoline fuel. Recently, new motor technologies and ethanol fuels have been introduced to the market, but potential health effects have not been thoroughly investigated. We developed and verified a coculture model composed of bronchial epithelial cells (ECs) and natural killer cells (NKs) mimicking the human airways to compare toxic effects between pure gasoline (E0) and ethanol-gasoline-blend (E85, 85% ethanol, 15% gasoline) exhaust emitted from a flexfuel gasoline car. We drove a steady state cycle, exposed ECs for 6 h and added NKs. We assessed exhaust effects in ECs alone and in cocultures by RT-PCR, flow cytometry, and oxidative stress assay. We found no toxic effects after exposure to E0 or E85 compared to air controls. Comparison between E0 and E85 exposure showed a weak association for less oxidative DNA damage after E85 exposure compared to E0. Our results indicate that short-term exposure to gasoline exhaust may have no major toxic effects in ECs and NKs and that ethanol as part of fuel for gasoline cars may be favorable. Highlights: The use of ethanol-gasoline blends may reduce dependency on fossil fuels. Toxicity of exhaust from modern gasoline cars has not yet been thoroughly investigated. Toxic effects of ethanol-gasoline blend exhaust are unknown. We exposed human bronchial epithelial cells for 6 h to fresh car exhaust. Exposure to exhaust from pure gasoline or ethanol-gasoline blend had only minor toxic effects.